If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7t + -2) + -1(-3t + 1) = 3(1 + -3) Reorder the terms: (-2 + 7t) + -1(-3t + 1) = 3(1 + -3) Remove parenthesis around (-2 + 7t) -2 + 7t + -1(-3t + 1) = 3(1 + -3) Reorder the terms: -2 + 7t + -1(1 + -3t) = 3(1 + -3) -2 + 7t + (1 * -1 + -3t * -1) = 3(1 + -3) -2 + 7t + (-1 + 3t) = 3(1 + -3) Reorder the terms: -2 + -1 + 7t + 3t = 3(1 + -3) Combine like terms: -2 + -1 = -3 -3 + 7t + 3t = 3(1 + -3) Combine like terms: 7t + 3t = 10t -3 + 10t = 3(1 + -3) Combine like terms: 1 + -3 = -2 -3 + 10t = 3(-2) Multiply 3 * -2 -3 + 10t = -6 Solving -3 + 10t = -6 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 10t = -6 + 3 Combine like terms: -3 + 3 = 0 0 + 10t = -6 + 3 10t = -6 + 3 Combine like terms: -6 + 3 = -3 10t = -3 Divide each side by '10'. t = -0.3 Simplifying t = -0.3
| 47-b=102 | | -5x=2x+14 | | y/5+4=-11 | | 3-7n=80 | | 938=q+721 | | .35(2.45x-5.82)=what | | 2(y+3)=y+2 | | 3s+7=42-5s | | P-56=-67 | | -x-1/2*x=9 | | 3a-1+2a+3+a= | | 4=k-12 | | 1/7x-1=0 | | 6w+2=6w+5 | | f(x)=x^3+4x^2-6x-24 | | 6x^2+4=10x+48 | | 2a+2b+2d= | | 165762751--8617526517517-75165265/762752751 | | 7+8x=4(2x-5) | | X^2-1=30 | | 3x*4y= | | g+g=46 | | 6x^2=10x+48 | | 286=h-291 | | 2.1(8.7-6.3x)=-9.6x-12.4 | | 5b-2c= | | 12x+112=1234 | | -2(x+6)+7(x-2)=x+1 | | Ln(x+3)=5.7 | | 3x+30=6x+48 | | (1/2b)^2 | | -3(2.47x+1.23)=9.83 |